2018
DOI: 10.3892/ol.2018.9110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of As2O3 on colorectal CSCs stained with ALDH1 in primary cell culture in�vitro

Abstract: Colorectal carcinoma (CRC) is one of the most common types of malignant tumor in humans, and its morbidity is on the increase in economically transitioning countries. Due to its high toxicity, the use of the Chinese Traditional Medicine arsenic (AsO) is limited. However, certain studies have reported that AsO induces differentiation of tumor cells, promotes tumor cell apoptosis and inhibits tumor cell proliferation, although the number of studies on the effects of AsO on cancer stem cells (CSCs) of CRC is limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…HH signaling is also necessary for the growth of CRC xenografts, recurrence, and induction of EMT necessary for metastases [ 169 ]. In contrast, arsenic trioxide, an anti‐leukemic drug known to inhibit the HH signaling pathway by targeting GLI1 [ 170 ], increased CRC‐SCs from patient samples [ 171 ].…”
Section: Cell Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…HH signaling is also necessary for the growth of CRC xenografts, recurrence, and induction of EMT necessary for metastases [ 169 ]. In contrast, arsenic trioxide, an anti‐leukemic drug known to inhibit the HH signaling pathway by targeting GLI1 [ 170 ], increased CRC‐SCs from patient samples [ 171 ].…”
Section: Cell Signaling Pathwaysmentioning
confidence: 99%
“…Suppresses GSK-3β/Wnt/β-catenin signaling [118] 4-Acetyl-antroquinonol B Suppresses LGR5/Wnt/β-catenin and JAK-STAT signaling [104] Anti-DLL4 antibodies Suppresses Notch signaling [158] Atractylenolide I Suppresses Akt/mTOR signaling [225] Baicalin Suppresses TGF-β/Smad signaling [244] Buparlisib (BKM120) Suppresses PI3K/Akt/mTOR signaling by inhibition of PI3K [210] CBB1003 Suppresses β-catenin/TCF signaling [119] Cucurbitacins Suppresses Notch signaling by downregulation of the expression of ADAM9 [142] Curcumin Suppresses JAK/STAT signaling by inhibition of STAT3 [195] Cyclopamine Suppresses HH signaling by inhibition of SMO [171] Dactolisib Suppresses PI3K/Akt/mTOR signaling by inhibition of PI3K [226] Diallyl trisulfide Suppresses Wnt/β-catenin signaling [105] Epigallocatechin-3-gallate Suppresses Wnt signaling by upregulation of GSK-3β [96] Evodiamine Suppresses Wnt and Notch signaling [150] Farnesyl dimethyl chromanol Suppresses Wnt/β-catenin signaling [102] FH535 Suppresses Wnt/β-catenin signaling [123] GO-Y030 Suppresses JAK/STAT signaling by inhibition of STAT3 [195] GW6471 Suppresses PPAR signaling (PPARα antagonist) [204] Honokiol Suppresses Notch signaling by inhibition of the levels of the γ-secretase complex [139] HZ8CV2 Suppresses Wnt signaling [126] IC-2 Suppresses Wnt signaling [111] JIB-04 Suppresses Wnt signaling by increasing the expression of AXIN1 and GSK3β [109] LY294002 Suppresses PI3K/Akt/mTOR signaling by inhibition of PI3K [209] α-Mangostine Suppresses Notch signaling [155] Metformin Suppresses PI3K/Akt/mTOR signaling by inhibition of mTOR [231] Miransertib Suppresses PI3K/Akt/mTOR signaling by inhibition of Akt [210] MK-2206 Akt inhibitor [212] Napabucasin (BBI-608) Suppresses JAK/STAT signaling by inhibition of STAT3 [196] NCB-0846 Suppresses Wnt signaling by block TNIK [57,114] Phenet...…”
Section: -077mentioning
confidence: 99%
“…Therefore, many chemotherapeutics kill the malignant tumor bulk population, but CSCs can survive and cause recurrence [28,50]. Ning K et al reported that ATO decreased tumor growth, the conversion from colorectal CSCs to CRC cells, and augmented the density of CSCs [51]. The function of CSCs in lung cancer is maintained through signaling pathways such as WNT, Notch, and Hedgehog [28].…”
Section: Anti-cancer Mechanismsmentioning
confidence: 99%
“…Increased expression of ALDH1 is associated with tumor progression and poorer outcomes in CRC patients ( 11 ). ALDH1 is abundant in tumor samples from patients with CRC ( 21 , 84 ), which can be used as a particular marker for CSCs of colorectal cancer ( 85 ), mainly including ALDH1A1, ALDH1B1, and ALDH1A3, are associated with poor prognosis and resistance to chemotherapy in colorectal cancer ( 86 88 ).…”
Section: Aldh1 and Various Solid Tumorsmentioning
confidence: 99%